Austenitic stainless steel surface strengthening treatment method
By combining laser impact treatment and ionic nitrogen-carbon co-permeation treatment on austenitic stainless steel, the problem of improving hardness and friction wear performance in the prior art is solved, and the comprehensive improvement of high hardness, good wear resistance and excellent corrosion resistance of stainless steel is achieved.
Patent Information
- Application Number
- CN202311223740.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-09-21
AI Technical Summary
While improving the hardness and friction wear properties of austenitic stainless steel, the prior art often affects its corrosion resistance and is difficult to meet the industrial requirements of corrosion resistance and wear resistance at the same time.
After laser shock treatment, ionic nitrogen carbon co-permeation is carried out, and the laser shock is used to induce a dynamic response of high strain rate, increasing the dislocation density and grain boundaries, thereby improving the diffusion efficiency of N and C atoms and forming a stable permeability layer.
While maintaining or improving the corrosion resistance of stainless steel, it significantly improves its hardness and friction wear performance, and obtains austenitic stainless steel with both high hardness and good wear resistance.
Smart Images

Figure CN119662970A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal material surface modification, in particular to a method for strengthening the surface of austenitic stainless steel. Background Art
[0002] Austenitic stainless steel has excellent corrosion resistance, good plasticity and toughness, and is widely used in marine, nuclear energy, chemical, medical, food and other industrial fields. However, due to the low hardness and poor wear resistance of austenitic stainless steel, it cannot be used in situations that require both good wear resistance and excellent corrosion resistance, which greatly limits its application range and forces manufacturers to seek expensive materials and production technologies to replace them, thereby greatly increasing corporate costs. Therefore, it is of great significance to study how to use surface modification technology to make stainless steel meet the industrial requirements of corrosion resistance and wear resistance at the same time.
[0003] Nitrocarburizing of stainless steel is to improve the hardness, wear resistance and corrosion resistance of stainless steel by co-diffusion of nitride and carbon elements on the surface of stainless steel. This treatment method can form a layer of nitride and carbide mixture on the surface of stainless steel, thereby improving the wear resistance of the material. However, simply performing ion nitrocarburizing on the surface of stainless steel has limited improvement on the hardness and friction and wear properties of stainless steel, and also affects the corrosion resistance of stainless steel. How to reduce the adverse effects of ion nitrocarburizing and obtain stainless steel with good corrosion resistance, good wear resistance and high hardness is a difficult problem that technicians in this field need to solve at this stage. Summary of the invention
[0004] The purpose of the present invention is to provide a method for surface strengthening treatment of austenitic stainless steel to solve the above problems existing in the prior art.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] One of the technical solutions of the present invention is a method for surface strengthening treatment of austenitic stainless steel, which comprises first subjecting the austenitic stainless steel to laser shock treatment, and then subjecting the austenitic stainless steel after the laser shock treatment to ion nitrocarburizing treatment; the impact energy of the laser shock treatment is 0-30J, and is not 0.
[0007] Further preferably, the impact energy of the laser shock treatment is 0-25J or 25-30J, and is not 0 and 25J.
[0008] Further preferably, the impact energy of the laser shock treatment is 8-22J or 27-30J.
[0009] Further preferably, the impact energy of the laser shock treatment is 20J or 30J.
[0010] More preferably, the impact energy of the laser shock treatment is 20J.
[0011] Furthermore, the number of impact layers in the laser impact treatment is 1 or 2, and the overlap rate is 40-60%.
[0012] Furthermore, the laser spot diameter of the laser shock treatment is 3-8 mm, the multiple shock frequency is 5-10 Hz, the pulse width is 16-25 ns, and the laser wavelength is 1064 nm.
[0013] Furthermore, before laser shock treatment, a 0.1 mm thick black tape was pasted on the surface of the austenitic stainless steel to be impacted as an absorption protection layer, and then a 1 mm thick running water was used as a constraint layer.
[0014] Furthermore, the insulation temperature of the ion nitrocarburizing treatment is 450-520° C., and the insulation time is 4-8 hours.
[0015] Furthermore, during the heat preservation process of the ion nitrocarburizing treatment, a mixed gas of ammonia, argon and methane is introduced at a pressure of 300 Pa. The flow ratio of ammonia, argon and methane is 20:9:1.
[0016] Furthermore, the heating process of the ion nitrocarburizing treatment includes two stages, namely, room temperature to 300°C, and 300°C to the insulation temperature. In the stage from room temperature to 300°C, a mixed gas of argon and methane is introduced, the flow ratio of argon and methane is 9:1, and the gas pressure is 200Pa; when the temperature is raised to 300°C, ammonia is introduced again, and the flow rate of ammonia gradually increases, that is, a mixed gas of ammonia, argon and methane is introduced in the stage from 300°C to the insulation temperature, so that the flow ratio of ammonia, argon and methane and the gas pressure in the furnace gradually increase with the increase of temperature. When the temperature reaches the insulation temperature, the gas pressure in the furnace reaches 300Pa, and the flow ratio of ammonia, argon and methane reaches 20:9:1.
[0017] Furthermore, the austenitic stainless steel is pretreated before the laser shock treatment, including: grinding the austenitic stainless steel, and then ultrasonically cleaning it in anhydrous ethanol.
[0018] Furthermore, the grinding is specifically grinding until the surface roughness of the austenitic stainless steel is ≤Ra3.2.
[0019] Furthermore, the grinding is performed sequentially using SiC sandpaper with mesh sizes of 180 to 2000.
[0020] Furthermore, the ultrasonic cleaning time is not less than 15 minutes.
[0021] Furthermore, before the ion nitrocarburizing treatment is performed on the austenitic stainless steel, the austenitic stainless steel after the laser shock treatment is polished again until the surface roughness of the austenitic stainless steel is ≤Ra1.6.
[0022] The second technical solution of the present invention: an austenitic stainless steel obtained by treating the surface strengthening treatment method of austenitic stainless steel.
[0023] The present invention first performs laser shock treatment on austenitic stainless steel, and then performs ion nitrocarburizing treatment on the austenitic stainless steel after laser shock treatment. Under the action of laser shock, the austenitic stainless steel undergoes a high strain rate dynamic response, so that the surface dislocations of the stainless steel increase, the grains are refined, and even nanocrystals are generated. The increase in dislocation density and grain boundaries provides more channels for the diffusion of N and C atoms in the subsequent ion nitrocarburizing treatment process, and the diffusion activation energy of atoms is reduced, which is conducive to the diffusion and reaction of elements, improves the diffusion efficiency, forms a stable diffusion layer, and promotes the generation of physical phases.
[0024] The present invention finds that the laser impact energy determines the degree of nano-crystal grains, dislocation density and defect degree of stainless steel surface layer. The degree of nano-crystal grains, dislocation density and defect degree affect the generation of S phase. The generation of S phase is promoted within the range of the degree of nano-crystal grains or dislocation density of a certain stainless steel, while the generation of S phase is inhibited within the range of the degree of nano-crystal grains or dislocation density of another stainless steel, thereby causing the comprehensive performance of the stainless steel nitrocarburized layer impacted by different laser impact energies to change in a quasi-sinusoidal curve (increases first, then decreases, and then increases again).
[0025] The present invention discloses the following technical effects:
[0026] The present invention first performs laser shock treatment on austenitic stainless steel, and then performs ion nitrocarburizing treatment on the austenitic stainless steel after laser shock treatment. The laser shock treatment and ion nitrocarburizing treatment cooperate with each other to effectively improve the hardness and friction and wear performance while taking into account the corrosion resistance of stainless steel, thereby obtaining austenitic stainless steel having both high hardness and good friction and wear performance and good corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0028] Figure 1The cross-sectional SEM images of the stainless steel samples of Examples 1-3 and Comparative Example 1 after grinding, polishing and corrosion by a corrosive solution, wherein (a) is Comparative Example 1, (b) is Example 1, (c) is Example 2, and (d) is Example 3;
[0029] Figure 2 The cross-sectional EDS images of the stainless steel samples of Examples 1-3 and Comparative Example 1 after grinding, polishing and corrosion by a corrosive solution, wherein (a) is Comparative Example 1, (b) is Example 1, (c) is Example 2, and (d) is Example 3;
[0030] Figure 3 The cross-section and surface microhardness change curves of stainless steel samples impacted with different laser impact energies after ion nitrocarburizing in Examples 1-3 and Comparative Example 1;
[0031] Figure 4 XRD patterns of stainless steel samples ion nitrocarburized with different laser shock energies in Examples 1-3 and Comparative Example 1;
[0032] Figure 5 The friction coefficient variation curves of the stainless steel samples impacted by different laser impact energies in Examples 1-3 and Comparative Example 1 after ion nitrocarburizing;
[0033] Figure 6 The electrochemical impedance spectroscopy (EIS) graphs of the stainless steel samples after ion nitrocarburizing with different laser shock energies of Examples 1-3 and Comparative Example 1;
[0034] Figure 7 is the equivalent circuit diagram of the impedance specimen;
[0035] Figure 8 Polarization curves of stainless steel samples after ion nitrocarburizing with different laser shock energies in Examples 1-3 and Comparative Example 1. DETAILED DESCRIPTION
[0036] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0037] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0038] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0039] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.
[0040] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0041] The austenitic stainless steel used in the following examples is 316 austenitic stainless steel that has not been solution treated, and its chemical composition is shown in Table 1:
[0042] Table 1 Chemical composition of 316 austenitic stainless steel (mass fraction, %)
[0043]
[0044] In the following examples, a LAMBER-H40 laser system is used to impact harden austenitic stainless steel. The system consists of an Nd:YAG pulse laser laser external optical path, an external control program, a multi-axis mechanical arm, a water confinement layer device, and a feedback controller.
[0045] In the following examples, an LDMC-100AZ fully automatic ion nitriding furnace was used to perform ion nitrocarburizing treatment on austenitic stainless steel.
[0046] Example 1
[0047] Stainless steel pretreatment: 316 austenitic stainless steel was processed into samples with a size of 50 mm × 50 mm × 5 mm, and polished in sequence with 180-2000 mesh SiC sandpaper until the surface finish was Ra3.2 (to ensure the uniformity of laser impact energy absorption). The samples were then placed in anhydrous ethanol and cleaned with ultrasonic waves for 15 minutes. After being taken out and blown dry, they were placed in a vacuum sample bag and evacuated for standby use.
[0048] Laser shock treatment: The pre-treated 316 stainless steel sample was subjected to laser shock treatment with 20J shock energy (laser single pulse energy), 1 shock layer, 50% overlap rate, 4mm laser spot diameter, 6Hz multiple shock frequency, 16ns pulse width, and 1064nm laser wavelength. Before the test, a 0.1mm thick black tape was attached to the surface of the sample to be impacted as an absorption protective layer, and 1mm thick running water was used as a constraint layer.
[0049] After the laser shock treatment, the 316 austenitic stainless steel sample after laser shock treatment was cut into small samples of 20 mm × 20 mm × 5 mm and polished to a finish of Ra1.6 (to ensure the uniformity of the later ion nitrocarburization layer structure).
[0050] Ion nitrocarburizing treatment: The laser-impacted and cut 316 austenitic stainless steel small sample is placed in an ion nitriding furnace for ion nitrocarburizing treatment. The holding temperature of the ion nitrocarburizing treatment is 480°C, the holding time is 5h, and a mixed gas of ammonia, argon and methane is introduced during the holding process (the flow ratio of ammonia, argon and methane is 20:9:1), and the gas pressure in the furnace is 300Pa. The heating process includes two stages, namely room temperature to 300°C, and 300°C to the holding temperature. A mixed gas of argon and methane (the flow ratio of argon and methane is 9:1) is introduced from room temperature to 300°C, and the gas pressure in the furnace is 200Pa; when the temperature is raised to 300°C, ammonia is introduced, and the flow rate of ammonia gradually increases, that is, a mixed gas of ammonia, argon and methane is introduced from 300°C to the insulation temperature, so that the flow ratio of ammonia, argon and methane and the gas pressure in the furnace gradually increase with the increase of temperature. When the temperature reaches 480°C, the gas pressure in the furnace reaches 300Pa, and the flow ratio of ammonia, argon and methane reaches 20:9:1.
[0051] Example 2
[0052] The same as Example 1, except that the impact energy of the laser shock treatment is 25J.
[0053] Example 3
[0054] The same as Example 1, except that the impact energy of the laser shock treatment is 30J.
[0055] Comparative Example 1
[0056] Stainless steel pretreatment: 316 austenitic stainless steel was processed into samples with a size of 50mm×50mm×5mm, and polished with SiC sandpaper of 180-2000 mesh to a surface finish of Ra3.2. The samples were then placed in anhydrous ethanol and cleaned with ultrasonic waves for 15 minutes. After being taken out and blown dry, they were placed in vacuum sample bags and evacuated for standby use.
[0057] The pretreated 316 austenitic stainless steel specimens were cut into small samples of 20 mm × 20 mm × 5 mm and polished to a surface finish of Ra1.6.
[0058] Ion nitrocarburizing treatment: After pretreatment and re-cutting and polishing, a small sample of 316 austenitic stainless steel is placed in an ion nitriding furnace for ion nitrocarburizing treatment. The holding temperature of ion nitrocarburizing treatment is 480℃, the holding time is 5h, and a mixed gas of ammonia, argon and methane is introduced during the holding process (the flow ratio of ammonia, argon and methane is 20:9:1), and the gas pressure in the furnace is 300Pa. The heating process includes two stages, namely room temperature to 300℃, and 300℃ to holding temperature. A mixed gas of argon and methane (the flow ratio of argon and methane is 9:1) is introduced from room temperature to 300°C, and the gas pressure in the furnace is 200Pa; when the temperature is raised to 300°C, ammonia is introduced, and the flow rate of ammonia gradually increases, that is, a mixed gas of ammonia, argon and methane is introduced from 300°C to the insulation temperature, so that the flow ratio of ammonia, argon and methane and the gas pressure in the furnace gradually increase with the increase of temperature. When the temperature reaches 480°C, the gas pressure in the furnace reaches 300Pa, and the flow ratio of ammonia, argon and methane reaches 20:9:1.
[0059] Compared with Example 1, the laser shock treatment is omitted in this comparative example (or the shock energy of the laser shock treatment is 0 J), and the 316 austenitic stainless steel is directly subjected to ion nitrocarburizing treatment.
[0060] Effect verification
[0061] 1. Morphology, structure and element distribution
[0062] The cross sections of the samples after ion nitrocarburizing in Examples 1-3 and Comparative Example 1 were ground and polished, and the cross sections were wiped and etched using Marble solution (CuSO4 4 g + HCl 20 mL + H2O 20 mL) as an etching solution to prepare metallographic samples.
[0063] The JEOL JSM-7600F field emission scanning electron microscope (SEM) and energy dispersive spectrometer (EDS) were used to observe the microstructure and analyze the composition of the surface layer of the samples of each embodiment and comparative example after being corroded by the corrosive solution.
[0064] Figure 1 The cross-sectional SEM images of the stainless steel samples of Examples 1-3 and Comparative Example 1 after grinding, polishing and corrosion by corrosive liquid, wherein (a) is Comparative Example 1, (b) is Example 1, (c) is Example 2, and (d) is Example 3. Figure 2The cross-sectional EDS images of the stainless steel samples of Examples 1-3 and Comparative Example 1 after grinding, polishing and corrosion by corrosive liquid are shown in Figure 1, where (a) is Comparative Example 1, (b) is Example 1, (c) is Example 2, and (d) is Example 3. Figure 1 It can be seen from the SEM images that the stainless steel samples without laser shock (Comparative Example 1) and the stainless steel samples subjected to laser shock with shock energies of 20J (Example 1), 25J (Example 2) and 30J (Example 3), after ion nitrocarburizing at 480°C and keeping warm for 5 hours, the thickness of the nitrocarburized layer are 27μm, 37μm, 32μm and 40μm respectively. In other words, with the increase of laser shock energy, the thickness of the nitrocarburized layer on the surface of the stainless steel sample first increases, then decreases slightly, and then increases again. From the morphology point of view, the nitrocarburized layers of (a) and (b) are relatively uniform, without obvious stratification and cracks, while (c) and (d) have obvious stratification and interfaces, but the nitrocarburized layer of (d) is thicker and has better uniformity. In addition, from Figure 2 It can be clearly seen from the EDS line scan that compared with the stainless steel matrix, the Fe content in the nitrocarburized layer of the stainless steel samples impacted by different laser shock energies is significantly reduced, but the Cr content is increased. With the increase of laser shock energy, the N content in the nitrocarburized layer on the surface of the stainless steel increases first, then slightly decreases, and then increases. The C content in (a) is very small and almost undetectable (because there is no laser shock, the surface dislocation is very small, so the C diffusion is very small), and the C content in the nitrocarburized layer in (b), (c) and (d) increases significantly in sequence, that is, with the increase of laser shock energy, the C content in the nitrocarburized layer gradually increases. In the nitrocarburized layers of (a), (b), (c) and (d), the N, C (except (a)), Fe and Cr content all show a sawtooth change. In the area where the N content decreases, the C content also decreases (except (a)), and the Fe and Cr content increases, and vice versa.
[0065] 2. Microhardness analysis
[0066] The cross section and surface of the sample after ion nitrocarburizing were polished to a mirror surface, and the cross section and surface microhardness of the nitrocarburized layer were tested using a HXD-1000 micro-Vickers hardness tester. The test pressure was 50 g and the holding time was 15 s.
[0067] Figure 3 The cross-section and surface microhardness change curves of the stainless steel samples after ion nitrocarburizing with different laser shock energies in Examples 1-3 and Comparative Example 1 are shown in FIG. Figure 3It can be seen that the highest hardness of the stainless steel samples with impact energy of 0J, 20J, 25J and 30J is on the outer surface of the sample, which are 1100, 1207, 981 and 1250.5HV0.05 respectively, while the matrix hardness is around 190HV0.05, that is, the highest hardness of the nitrocarburized layer is 5.5 to 6.5 times the hardness of the matrix. Except for the surface (the surface hardness is the highest at 30J), at the same distance from the sample surface, the stainless steel sample with laser impact energy of 20J has the highest hardness (that is, the hardness curve is on the far right), and the hardness gradient of the nitrocarburized layer is relatively small, and the hardness gradient is almost 0 at 25-35μm, which greatly reduces the risk of nitrocarburized layer falling off. The stainless steel sample with impact energy of 30J also has a higher hardness, second only to the sample with laser impact energy of 20J, but its hardness gradient is large and easy to fall off. The samples with the smallest hardness are those with impact energy of 0J and 25J, and their hardness curves are almost overlapping.
[0068] 3. Phase analysis of the permeation layer
[0069] Before phase detection, the surface of the sample after ion nitrocarburizing was polished to a mirror surface, and the phase analysis of the permeation layer of the stainless steel sample was carried out using a Japanese Rigaku Ultima IV Cu Ka target X-ray diffractometer. According to the relevant organizational PDF card, the angle was selected to be 30° to 100°. The speed was selected to be 5° / min, the high voltage was selected to be 40kV, and the test current was selected to be 40mA.
[0070] Figure 4 The XRD patterns of stainless steel samples ion nitrocarburized with different laser shock energies in Examples 1-3 and Comparative Example 1 are shown. Figure 4 It can be seen that the stainless steel samples that have been laser impacted with impact energies of 0J, 20J, 25J and 30J, respectively, have a diffusion layer composed of three phases: γ phase, S phase and Cr2N phase. Among them, the phase composition of the diffusion layer of the stainless steel samples with impact energies of 20J and 30J is not much different. They are mainly composed of S phase, with a small amount of γ phase and Cr2N phase. The phase composition of the diffusion layer of the stainless steel samples with impact energies of 0J and 25J is not much different. The amount of γ phase increases significantly, the amount of S phase decreases significantly, and there is also a small amount of Cr2N phase. The γ phase is the austenite phase, which has low hardness and poor wear resistance, but good corrosion resistance. The S phase is a saturated γ phase. N Phase, has good corrosion resistance and wear resistance, while Cr2N phase has high hardness but poor corrosion resistance. Through the comparative analysis of the content of each phase in the carburized layer of stainless steel samples with impact energy of 20J and 30J and stainless steel samples with impact energy of 0J and 25J, it is found that the absolute content of S phase in the former is much higher than that in the latter, the content of Cr2N phase is basically the same, and the absolute content of γ phase in the latter is higher than that in the former.
[0071] S phase is divided into SN phase (N element diffuses into γ phase), S C (formed by the diffusion of C elements into the γ phase) and S NC phase ((N and C elements diffuse into the γ phase at the same time), the S phase formed in the austenitic stainless steel after laser shock treatment + ion nitrocarburizing treatment in the present invention is S NC Phase. S N High phase hardness, poor toughness, easy to fall off; S C The phase toughness is good, the hardness is low, and the wear resistance is slightly poor. NC The phase combines the advantages of the two phases very well, so that the diffusion layer has both high hardness and good toughness, as well as good corrosion resistance.
[0072] 4. Friction and wear performance analysis
[0073] Before the friction and wear test, the sample surface after ion nitrocarburizing was first polished to a mirror surface. The experimental equipment used was a HT-2005 testing machine with a load of 10N, a wear time of 1800s, a friction pair of 6mm diameter WC balls, and a rotation speed of 318rpm.
[0074] Figure 5 The friction coefficient change curves of stainless steel samples ion nitrocarburized with different laser shock energies in Examples 1-3 and Comparative Example 1 are shown. There are many factors that affect the change of friction coefficient, mainly surface hardness, phase structure and its ratio, roughness, etc. Figure 5 It can be seen that the friction coefficient of the stainless steel sample with a laser impact energy of 30J is the lowest, about 0.53-0.65, which is related to its higher hardness and the thickest carburized layer. The second is the sample with a laser impact energy of 20J, whose friction coefficient is about 0.52-0.68. Figure 5 It can be seen that their friction coefficients increase with the extension of friction time. The friction coefficient of the stainless steel sample with an impact energy of 25J is the highest, which is about 0.73 in steady state. This is because of its lower hardness and roughness (polishing before the experiment). The friction coefficient of the sample without laser shock first increases and then decreases. The reason why the friction coefficient of the above stainless steel samples fluctuates greatly is that the surface roughness of the stainless steel samples caused by laser shock is relatively large.
[0075] 5. Electrochemical analysis
[0076] Before the electrochemical test, the surface of the sample after ion nitrocarburization was first polished to a mirror surface. The electrochemical test of Tafel polarization curve and Nyquist diagram was carried out on the stainless steel samples of Examples 1-3 and Comparative Example 1 using Shanghai Chenhua CHI660E electrochemical workstation, with the stainless steel sample as the working electrode, the auxiliary electrode as the platinum electrode, the reference electrode as the saturated calomel electrode (SCE), and the solution as 3.5% NaCl solution.
[0077] Figure 6 The electrochemical impedance spectroscopy (EIS) diagrams of the stainless steel samples after ion nitrocarburizing with different laser shock energies of Examples 1-3 and Comparative Example 1 are shown in FIG. Figure 6 It can be seen that in 3.5% NaCl solution, the Nyquist plots of the surface passivation film of the stainless steel samples after nitrocarburizing with different laser shock energies of 0J, 20J, 25J and 30J respectively show a single capacitive arc. The largest capacitive arc is the sample with a laser shock energy of 20J, followed by the sample with an impact energy of 30J. The capacitive arc of the samples with impact energies of 0J and 25J is the smallest. The larger the curvature radius of the capacitive arc, the greater the capacitance of the passivation film, the greater the density, and the better the corrosion resistance. Figure 7 The equivalent circuit diagram of the impedance sample shown in the figure is used to fit and analyze the EIS data using the ZsimpWin software, where Rs is the solution resistance, Rt is the charge transfer resistance, CPE represents the constant phase angle element of the double layer capacitance characteristics, and its impedance (Z CPE )for:
[0078] Z CPE =(j ω -n ) / Y0 (1)
[0079] Where: ω is the angular frequency, rad / s; Y0 is the CPE parameter, F / (sn -1 cm 2 ); n is a dimensionless index, which indicates the degree to which CPE deviates from pure capacitance. The closer its value is to 1, the closer its passivation film is to the ideal capacitance. Figure 7 The fitting curve fits the measured curve very well, and the fitting error of each component is within 5%, indicating that the equivalent circuit basically reflects the actual corrosion behavior.
[0080] Table 2
[0081]
[0082] The fitting parameters of the equivalent circuit are shown in Table 2. It can be seen from Table 2 that when the laser shock energy is 20J, the passivation film of the stainless steel nitrocarburizing layer has the highest charge transfer resistance and the lowest double-layer capacitance, followed by the stainless steel sample with a laser shock energy of 30J, while the stainless steel samples with laser shock energies of 0J and 25J have the lowest charge transfer resistance and the highest double-layer capacitance. This shows that under the nitrocarburizing conditions, the passivation film formed on the surface of the stainless steel sample with a laser shock energy of 20J is thicker, has the best density and corrosion resistance, and can effectively hinder the penetration and migration of reactive ions, followed by the stainless steel sample with a laser shock energy of 30J, while the stainless steel samples with laser shock energies of 0J and 25J have the worst corrosion resistance, which is consistent with the results of the polarization curve test.
[0083] Figure 8 Table 3 shows the polarization curves of the stainless steel samples after ion nitrocarburizing with different laser shock energies in Examples 1-3 and Comparative Example 1. Figure 8 The electrochemical parameters obtained by fitting the polarization curve are Figure 8 The polarization curves of the stainless steel samples with different laser shock energies and the electrochemical parameters fitted by the polarization curves in Table 3 clearly show that the polarization curves of the nitrocarburized layer of the stainless steel samples with different laser shock energies do not show obvious passivation zones. P ) )(0.948μA and 0.852μA respectively) and self-corrosion potential (E corr The corrosion resistance of stainless steel samples with laser impact energy of 20J and 30J is the best, which also confirms the results of electrochemical impedance spectroscopy.
[0084] Table 3
[0085]
[0086] The combined treatment process of laser shock and ion nitrocarburizing has a significant effect on the corrosion resistance, friction and wear properties and microhardness of stainless steel. Based on the above results, the following analysis is made: laser shock causes dislocations and other defects to entangle or aggregate at specific locations, thereby affecting the diffusion of N and C elements and the formation of nitrides, causing nitrogen and carbon atoms to aggregate along specific directions or interfaces to form Figure 2The jagged distribution of N and C elements in the nitrocarburized layer. The reason why the changes of N and C elements are opposite to those of Cr and Fe elements may be that during nitrocarburizing, N and C atoms enter the metal lattice and form a substantial solid solution compound with metal atoms. In this compound, N and C atoms will replace the positions of some Cr and Fe atoms, resulting in a relative reduction of Cr and Fe elements in the nitrocarburized layer. In terms of phase composition, by comparing the content of each phase in the nitrocarburized layer of stainless steel samples with impact energies of 20J and 30J and those with impact energies of 0J and 25J, it was found that the S phase content in the former was much higher than that in the latter, the Cr2N content was basically the same, and the absolute content of γ phase in the latter was higher than that in the former. That is to say, in the composite strengthening of 316 stainless steel by laser shock plus ion nitrocarburizing (keeping at 480℃ for 5h), the generation or decomposition of S phase may be related to the magnitude of the impact energy. Using impact energy values within a certain range (such as 20J) for laser shock is conducive to the generation of S phase or inhibits its decomposition, while using impact energy values within another range (such as 25J) for laser shock may slow down the generation of S phase or promote its decomposition process.
[0087] Through the analysis of the performance data of the cross-sectional microhardness, friction and wear test and electrochemical experiment of the nitrocarburized layer, it is found that the stainless steel sample with an impact energy of 20J not only has the highest hardness and the lowest friction coefficient, but also has the best corrosion resistance, followed by the sample with a laser impact energy of 30J. The sample with the smallest hardness, the lowest friction coefficient and the worst corrosion resistance is the sample with an impact energy of 25J. From the phase analysis, the present invention finds that this may be related to the content of the S phase. The content of the S phase in the stainless steel samples with impact energies of 20J and 30J is significantly higher than that in the stainless steel samples with impact energies of 0J and 25J. This may be the reason why it has both high hardness and wear resistance and good corrosion resistance. Under the process conditions of the present invention, within the range of 0-30J laser impact energy, with the increase of laser impact energy, the cross-sectional hardness, friction coefficient and corrosion resistance of the stainless steel nitrocarburized layer all show a quasi-sine curve change (first increase, then decrease and then increase), with obvious peaks and troughs. Compared with the previous result analysis, the change in the performance of the stainless steel nitrocarburized layer may be mainly related to the content and distribution of the S phase.
[0088] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for surface strengthening of austenitic stainless steel, characterized in that: The austenitic stainless steel is firstly subjected to laser shock treatment, and then the austenitic stainless steel subjected to laser shock treatment is subjected to ion nitrocarburizing treatment; the impact energy of the laser shock treatment is 0-30J and is not 0.
2. The method for surface strengthening of austenitic stainless steel according to claim 1, characterized in that: The number of impact layers in the laser impact treatment is 1 or 2, and the overlap rate is 40-60%.
3. The method for surface strengthening of austenitic stainless steel according to claim 1, characterized in that: The holding temperature of the ion nitrocarburizing treatment is 450-520° C., and the holding time is 4-8 hours.
4. The method for surface strengthening of austenitic stainless steel according to claim 1, characterized in that: During the heat preservation process of the ion nitrocarburizing treatment, a mixed gas of ammonia, argon and methane is introduced at a pressure of 300 Pa.
5. The method for surface strengthening of austenitic stainless steel according to claim 4, characterized in that: The flow ratio of ammonia, argon and methane is 20:9:
1.
6. The method for surface strengthening of austenitic stainless steel according to claim 1, characterized in that: Before laser shock treatment, the austenitic stainless steel is pretreated, including grinding the austenitic stainless steel and then ultrasonically cleaning it in anhydrous ethanol.
7. The method for surface strengthening of austenitic stainless steel according to claim 6, characterized in that: The grinding is specifically grinding until the surface roughness of the austenitic stainless steel is ≤Ra3.
2.
8. The method for surface strengthening of austenitic stainless steel according to claim 6, characterized in that: The ultrasonic cleaning time is not less than 15 minutes.
9. Austenitic stainless steel obtained by treatment according to the surface strengthening treatment method of austenitic stainless steel according to any one of claims 1 to 8.
Citation Information
Patent Citations
Method for preparing composite coating with high film-base binding force on surface of titanium alloy
CN112323013A
Cooperative control method for high hardness and low brittleness of superhigh-strength stainless steel surface layer
CN116219443A
Processing method of corrosion-resistant austenitic stainless steel
CN116536505A
Method of metal performance improvement and protection against degradation and suppression thereof by ultrasonic impact
US20070068605A1
Cited By
Austenitic stainless steel surface wear-resistant strengthened layer and preparation method thereof
CN122542973A